Out-of-hospital and Inter-hospital Under-triage to Designated Tertiary Trauma Centers among Injured Older Adults: A 10-year Statewide Geospatial-Adjusted Analysis. (2nd November 2017) - Garwe, Tabitha; Stewart, Kenneth; Stoner, Julie; Newgard, Craig D.; Scott, Melissa; Zhang, Ying; Cathey, Timothy; Sacra, John; Albrecht, Roxie M.
Abstract: Objective : While out-of-hospital under-triage of seriously injured older adults to tertiary trauma centers has long been acknowledged, no study has adjusted for place of injury or evaluated the extent of inter-facility under-triage. We sought to determine distance and confounder adjusted odds of treatment at a tertiary trauma center (TTC) for older adult trauma patients compared to younger trauma patients, for patients transported from the scene of injury and those transferred from a non-tertiary trauma (NTTC) center.Methods : This was a retrospective cohort study utilizing data from a statewide trauma registry reported over a 10-year period (2005–14). The outcome of interest was treatment at an American College of Surgeons or state-designated Level I/II trauma center (TTC). The predictor variable of interest was age group (> = 55 years vs. < 55 years). Covariates of interest included patient demographics, clinical characteristics and various distance measures calculated based on the patient's injury location.Results : 84 930 patients met study criteria. Of these 42% (35659) were 55 years and older with an average age of 74 years (SD, 11.6). Older adult patients were on average, injured slightly farther away from a TTC (median distance, 34 vs. 29 miles, p < 0.001). Among patients initially presenting to NTTCs, older adults were significantly more likely to be transferred to another NTTC (53% vs. 34%). After adjusting for confounders and distance measures, older adults were less likely to be treated at TTCs overall (OR = 0.54, 95% CI: 0.52–0.56), whether transported by EMS from the scene of injury (OR = 0.47, 95% CI: 0.44–0.50) or via inter-facility transfer (OR = 0.63, 95%CI: 0.59–0.68).Conclusions : Injured older adults face significant under-triage to TTCs whether by EMS from the scene of injury or via transfer from NTTCs. Adjusting for proximity of injury to a TTC does not alter these findings.